1977
DOI: 10.1017/s0043174500033324
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Atrazine in Three Gramineae Subfamilies

Abstract: Inhibition and subsequent recovery of net CO2exchange (NCE) by single leaves of 53 grass species of the subfamilies Festucoideae, Panicoideae, and Eragrostoideae was monitored following limited root uptake of atrazine [2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine]. Rates of NCE recovery were correlated with rates of14C-atrazine metabolism in leaf sections of festucoid and panicoid grasses but not eragrostoid grasses. Rates of NCE recovery among the nine festucoid and 12 eragrostoid species tested did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 25 publications
(41 reference statements)
2
34
0
Order By: Relevance
“…Photosynthesis, measured as the rate of CO 2 uptake, was found to recover gradually in maize after being removed from simazine exposure [4]. These results were further verified in several grass species exposed to atrazine by measuring CO 2 uptake in whole leaves [6]. These results were further verified in several grass species exposed to atrazine by measuring CO 2 uptake in whole leaves [6].…”
Section: Introductionmentioning
confidence: 58%
“…Photosynthesis, measured as the rate of CO 2 uptake, was found to recover gradually in maize after being removed from simazine exposure [4]. These results were further verified in several grass species exposed to atrazine by measuring CO 2 uptake in whole leaves [6]. These results were further verified in several grass species exposed to atrazine by measuring CO 2 uptake in whole leaves [6].…”
Section: Introductionmentioning
confidence: 58%
“…Atrazine acts by inhibiting photosystem-II of photosynthesis through competitive and noncovalent binding of the QB site of the D1 protein (Jensen et al, 1977;Jursinic and Stemler, 1983;Shimabukuro et al, 1970). Consequently, inhibition is reversible immediately upon removal of atrazine, and recovery of both terrestrial and aquatic plant communities under a variety of conditions has been demonstrated (Jensen et al, 1977;Shimabukuro et al, 1970;Klaine et al, 1996;Brain et al, 2012aBrain et al, , 2012bBrockway et al, 1984;Hughes et al, 1988;Jones et al, 1986;Juttner et al, 1995;Teodorović et al, 2012;Mohammad et al, 2008Mohammad et al, , 2010Stay et al, 1989;Vallotton et al, 2008). In a variety of algal species, both biochemically and physiologically, recovery of photosynthesis and growth rate occur immediately, reaching control levels within hours following exposure to atrazine at concentrations much higher than typically encountered in situ (250-1000 μg/L) (Vallotton et al, 2008;Brain et al, 2012aBrain et al, , 2012bHughes et al, 1988).…”
Section: Inertia Explained By Variable Group and By Individual Variablesmentioning
confidence: 99%
“…Atrazine inhibits photosynthesis by blocking the flow of electrons between photosystem II (PSII) and plastoquinone (Forney and Davis, 1981); however, the binding interaction is competitive, noncovalent, and reversible (Jensen et al, 1977;Jursinic and Stemler, 1983). Consistent with the mode of action, several studies have documented rapid recovery of aquatic plants from atrazine exposure when it is removed from the aquatic medium (Brain et al, 2012;Hughes et al, 1988;Vallotton et al, 2008).…”
Section: Introductionmentioning
confidence: 98%